Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Lim x->0 (xcosx-log(1+x))/x^2.Limx->0 (xcosx - x )/x^2 (by elimination )Lim x->0 (cosx - x)/xWhich is finally equal to zero but by using expansion and L hospital`s rule i get the answer 1/2.What is wrong in this method ?

Lim x->0 (xcosx-log(1+x))/x^2.Limx->0 (xcosx - x )/x^2 (by elimination )Lim x->0 (cosx - x)/xWhich is finally equal to zero but by using expansion and L hospital`s rule i get the answer 1/2.What is wrong in this method ?

Grade:12

1 Answers

Vikas TU
14149 Points
4 years ago
Here if U are using log expansion then write for cos function too.
lim x-> 0 becomes:
 
=> (x(1-x^2/2) – (x – x^2/2))/x^2
=> (1-x^2/2) – 1 + x/2)/x
=> (-x^2/2) + x/2)/x
=> (-x/2 + 0.5)/1
=> 0.5 would be the final ansswer.
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free